First analysis of the ν2+ν7 and ν2+ν9 and ν2+ν6 combination bands of HNO3: evidence of perturbations due to large amplitude OH torsion in the 2191 excited state. (18th August 2022) - Perrin, A.; Manceron, L.; Armante, R.; Kwabia-Tchana, F.; Roy, P.; Doizi, D.
Abstract : This paper is the first of two back-to-back works, whose goal is to update the existing line positions and intensities spectroscopic parameters for the 5.8 µm region of nitric acid in the HITRAN or GEISA spectroscopic databases. This first study is devoted to the generation of first linelists for the ν2 +ν9 -ν9, ν2 +ν7 -ν7 and ν2 +ν6 -ν6 hot bands in the 5.8 µm region, whereas the second study will concern the positions and intensities for the ν2 band centred at 1709.567 cm −1 . High-resolution Fourier transform spectra were recorded in the 5.8 µm and in the 4.2–4.6 µm spectral ranges. The identification of the ν2 +ν9, ν2 +ν7 and ν2 +ν6 bands of HNO3 at 2165.0036, 2285.9657 and 2351.216 cm −1, respectively, was performed, and several assignments were confirmed by searching for ν2 +ν9 -ν9 and ν2 +ν7 -ν7 transitions within those of ν2 at 5.8 µm. Both ν2 +ν6 and ν2 +ν9 bands are highly perturbed. Surprisingly, both ν2 +ν9 and ν2 +ν9 -ν9 bands exhibit large amplitude torsional splittings of ∼0.043 cm −1 . This is presumed to be due to the existence of an anharmonic resonance that couples together the 2 1 9 1 energy levels with those of a dark state involving high excitation in the ν9 large amplitude OH torsional mode. GRAPHICAL ABSTRACT: UF0001